2015
DOI: 10.1016/j.apgeog.2014.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Mobility in the mangroves: Catch rates, daily decisions, and dynamics of artisanal fishing in a coastal commons

Abstract: This paper integrates institutional theories of the commons with insights from geography and human behavioral ecology to explore the spatial and temporal dynamics of artisanal fishing in Ecuador's coastal mangrove swamps. The focus is on the cockle fishery commons characterized by a mixture of formal institutional arrangements and an informal division of fishing space that partially influences fisher decisions about where and when to fish. Individual decisions are further explained to a certain degree by the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 68 publications
0
12
0
2
Order By: Relevance
“…; Johnson et al . ; Beitl , ; Lynham ). Moreover, large‐scale commercial pelagic fishing fleets, targeting mobile and sparse (high exploration difficulty and low exploitation potential) pelagic species such as tuna and billfish with trawls or long‐lines, showed high degrees of collective searching (Mangel & Clark ; Dreyfus‐Leon & Kleiber ; Curtis & McConnell ; Gaertner & Dreyfus‐Leon ; Dreyfus‐Leon & Gaertner ; Girardin et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…; Johnson et al . ; Beitl , ; Lynham ). Moreover, large‐scale commercial pelagic fishing fleets, targeting mobile and sparse (high exploration difficulty and low exploitation potential) pelagic species such as tuna and billfish with trawls or long‐lines, showed high degrees of collective searching (Mangel & Clark ; Dreyfus‐Leon & Kleiber ; Curtis & McConnell ; Gaertner & Dreyfus‐Leon ; Dreyfus‐Leon & Gaertner ; Girardin et al .…”
Section: Resultsmentioning
confidence: 99%
“…Other mixed strategy cases can be better explained through mechanisms unaccounted for in our framework. In some SES cases the ability to defend a territory or search collectively related to membership in an exclusive group requiring strong social ties (Gatewood ; Carpenter & Seki ; Beitl , ) or to a historical separation of communities (Krause & Ramos ), stressing the relevance of social norms, social and personal capital, social identity, the need for repeated interactions and path dependencies of property rights. Additionally, mixed strategies may be the result of different top‐down governmental controls emerging from development of a fishery under different political systems (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…For marine areas, for which most SCP software was developed, this tends not to be a problem (Abecasis, Afonso & Erzini, 2015). Studies from Ecuador (Beitl, 2015), Malaysia (Teh, Teh & Meitner, 2012), and Brazil (Begossi, 2006) found that marine fishers' spatial behaviours are mostly based on a stable routine. In the case of floodplain socioecological systems, however, this is challenging (Abell et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…These concessions specify the community's rights to use the mangrove ecosystem for artisanal fishery. In communities where the concessions have been implemented, local associations of fishermen have privileged access for fishing within the boundaries of their area (Beitl, 2015).…”
Section: Introductionmentioning
confidence: 99%